2018
DOI: 10.1080/16549716.2018.1435344
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer services in Vietnam: a scoping review

Abstract: Background: Breast cancer incidence has been increasing consistently in Vietnam. Thus far, there have been no analytical reviews of research produced within this area. Objectives: We sought to analyse the nature andextent of empirical studies about breast cancer in Vietnam, identifying areas for future research and systemsstrengthening. Methods: We undertook a scoping study using a five-stage framework to review published and grey literature in English and Vietnamese on breast cancer detection, diagnosis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…As shown within this, and many other studies (24), cancer requires time-intensive care for prolonged periods in specialised and centralised oncology hospitals. Cancer remains poorly understood in Vietnam, and there is low awareness concerning what to expect within both treatment and care (5).…”
Section: Discussionsupporting
confidence: 57%
“…As shown within this, and many other studies (24), cancer requires time-intensive care for prolonged periods in specialised and centralised oncology hospitals. Cancer remains poorly understood in Vietnam, and there is low awareness concerning what to expect within both treatment and care (5).…”
Section: Discussionsupporting
confidence: 57%
“…Population or targeted screening campaigns remain limited, and none of the women in our study entered the health system through a screening programme. While there have been a number of one-off screening campaigns8 and different organisations such as the Bright Future Foundation have recently funded and purchased a breast cancer screening bus, this service remains largely inaccessible for many women. Interestingly, more women seemed to be aware of screening services for cervical cancer, and this may represent a model of good practice from which to build on.…”
Section: Discussionmentioning
confidence: 99%
“…Research surveying and interviewing healthcare providers (HCPs) has indicated that there is a need for breast cancer systems strengthening across all levels of the Vietnamese health system and that lower levels of the health system often lack sufficient capacity to detect and diagnose breast cancer 7. The absence of qualitative data on breast cancer services from the perspective of women with a breast cancer diagnosis8 limits the effective planning of breast cancer services.…”
Section: Introductionmentioning
confidence: 99%
“…In women, breast cancer is considered to be the main cause of women's deaths worldwide (Bray et al, 2018). There were more than two million newly diagnosed as breast cancer in women worldwide in 2018 (Bray et al, 2018;Jenkins et al 2018). There will be an estimated 18.1 million new cancer cases and 9.6 million cancer deaths in 2018.…”
Section: Introductionmentioning
confidence: 99%